Adenosine/adenosine type 1 receptor signaling pathway did not play dominant roles on the influence of sodium–glucose cotransporter 2 inhibitor in the kidney of bovine serum albumin‐overloaded streptozotocin‐induced diabetic mice. Issue 6 (9th March 2022) - Shimada, Keiji; Kanasaki, Keizo; Kato, Makoto; Ogura, Yoshio; Takagaki, Yuta; Monno, Itaru; Hirai, Taro; Kitada, Munehiro; Koya, Daisuke
Abstract: Aims/Introduction: Sodium–glucose cotransporter 2 inhibitors (SGLT2i) have been shown to display excellent renoprotective effects in diabetic kidney disease with macroalbuminuria/proteinuria. Regarding the renoprotective mechanism of SGLT2i, a sophisticated hypothesis was made by explaining the suppression of glomerular hypertension/hyperfiltration through the adenosine/adenosine type 1 receptor (A1R) signaling‐mediated restoration of the tubuloglomerular feedback mechanism; however, how such A1R signaling is relevant for renoprotection by SGLT2i in diabetic kidney disease with proteinuria has not been elucidated. Materials and Methods: Streptozotocin‐induced diabetic CD‐1 mice were injected with bovine serum albumin (BSA) and treated with SGLT2i in the presence/absence of A1R inhibitor administration. Results: We found that the influences of SGLT2i are essentially independent of the activation of A1R signaling in the kidney of BSA‐overloaded streptozotocin‐induced diabetic mice. BSA‐overloaded diabetic mice showed the trend of kidney damage with higher glomerular filtration rate (GFR) and the significant induction of fibrogenic genes, such as transforming growth factor‐β2 and collagen type III. SGLT2i TA‐1887 suppressed diabetes‐induced GFR in BSA‐overloaded diabetic mice was associated with the significant suppression of transforming growth factor‐β2 and collagen type III; A1R‐specific inhibitor 8‐cyclopentyl‐1, 3‐dipropylxanthine did not cancel the effects of TA‐1887 on either GFR or associated gene levels. Both TA‐1887 and 8‐cyclopentyl‐1, 3‐dipropylxanthine‐treated BSA‐overloaded diabetic mice showed suppressed glycated hemoglobin levels associated with the increased food intake. When analyzing the association among histological evaluation, GFR and potential fibrogenic gene levels, each group of mice showed distinct correlation patterns. Conclusions: A1R signaling activation was not the dominant mechanism on the influence of SGLT2i in the kidney of BSA‐overloaded diabetic mice. Abstract : Utilizing a bovine serum albumin‐overloaded proteinuric mouse model, we found that the influences of sodium–glucose cotransporter 2 inhibitors are essentially independent of the activation of adenosine type 1 receptor signaling in the kidney of bovine serum albumin‐overloaded streptozotocin‐induced diabetic mice. When analyzing the association among histological evaluation, glomerular filtration rate and potential fibrogenic gene levels, each group of mice showed distinct correlation patterns.